Feedback dan Media Sosial Kepala Daerah di Sulawesi Selatan: (Studi pada Akun Instagram Ramdhan Danny Pomanto, Adnan Purichta Ichsan, Taufan Pawe, dan Indah Putri Indriani) - Silahuddin Sila Genda; Hafied Cangara; Alimuddin Unde; Muliadi Mau (STAI Bumi Silampari, 2025)
This study aims to analyse the responses (feedback) given by netizens to four social media accounts of regional heads in South Sulawesi. Qualitative research with a descriptive approach was conducted with a focus on the scope of managing responses (feedback) from the public on the Instagram social media accounts of Makassar Mayor Ramdhan Danny Pomanto, Parepare of Mayor Taufan Pawe, Gowa of Regent Adnan Purichta Ichsan, and North Luwu of Regent Indah Putri Indriani for the period June – September 2023. Data were analysed using the NVivo 12 Plus application tool. The results showed that the management of feedback on the Instagram accounts of the four regional heads was not optimal because there was no SOP (Standard Operating Procedure) format given by each regional head to the account manager, although some feedback was answered via direct messege as well as with a pattern through the scope of related agencies to find solutions. The form of feedback used by followers on the regional heads' Instagram accounts consists of positive, negative, and neutral feedback.